P6.017 The Challenges of Introducing a Software-Based Intervention to Increase STI and HIV Testing Among Gay and Bisexual Men. (13th July 2013) - Callander, D; Bourne, C; Ramanathan, V; Wit, J de; Guy, R
Abstract : Background: Information technology is being used increasingly in sexual health services to improve clinical efficiencies and sexual health management. While past research has demonstrated the effectiveness of such interventions, little attention has been paid to their use in general practise. We describe the challenges of introducing a sexual health information technology package in nine general practise clinics with medium to high case loads of gay or bisexual men. Methods: As part of 'The eTEST Project', an integrative information technology package was developed containing an electronic risk assessment, clinician prompts to offer testing, SMS testing recalls, and electronic auditing functions. The software was introduced progressively starting in November 2011 with meeting and field notes gathered during clinic visits before, during and after implementation. Using these data, a thematic analysis was undertaken with a focus on identifying the challenges of introducing new technology in a clinical context. Results: Three dominant themes were identified in the meeting and field note data. The first of these, 'time management', describes the perceived risks to time-efficient consults that doctors and staff feared employing a new tool and collecting additional information could pose. Second, 'administrative limitations', a theme most common among practise managers, raises issues of increased demand on already burdened administrative supports. The final theme, 'technological requirements', is characterised by doctor's concerns over the additional burden of learning and using new software and troubleshooting technical issues. Conclusions: The results highlight common concerns and fears among clinical staff around the use of new technologies in general practise. Not only does this provide an opportunity for comparisons with the traditional hurdles to clinical health interventions but it is also the first step towards overcoming such obstacles. More broadly, these findings can inform future technology interventions of a similar nature in general practise.